“Time Never Worked That Way:” Toni Morrison’s Disruption of Historical Chronology in Beloved - Mahmoudi , Yazdan; Rezapoorian , Sayyed Navid Etedali (American & British Studies Annual, 2025)
This article reads Toni Morrison’s Beloved (1987) as a form, intervention and expansion of Black temporality. Rather than retelling history in linear time, Morrison uses a recursive, ghosted narrative that deconstructs the divide between past and present. Drawing on Tao Leigh Goffe's concept of “maroon time,” the novel is here read as a refusal of Enlightenment chrononormativity as well as racial capitalism's demand for closure, progress, and resolution. With Morrison's free indirect discourse, fractured pace, and spectrality, Beloved inscribes time as trauma, survival, and resistance. The novel re-writes the Black womb as a site not of reproduction but of temporal disjunction, its form possessing a fugitive beat that shatters Western historiography. Morrison extends the grammar of Black narration by architecting a temporality which is incomplete, relational, and speculative, rendering the novel an ethical and political site of refusal.